Late Roman Dorset black-burnished ware (BB1) : a corpus of forms and their distribution in Southern Britain, on the continent and in the Channel Islands - Lyne, M. A. B., (Archaeopress Roman archaeology., 2022)
Much has been written about Roman Dorset Black-Burnished Ware (BB1) and its Late Iron Age Durotrigian origins since the industry was first recognised at the end of the 1960s. However, this has mostly focused on the forms produced and distributed during the 1st to 3rd centuries. This publication covers those of the late 3rd to early 5th century.